The Minority Language Debate: The Case of Yiddish in the Dutch Language Landscape - Hamans, Camiel (Zakład Studiów Niderlandzkich i Południowoafrykańskich, Wydział Anglistyki UAM / Wydawnictwo Naukowe Exemplum, 2006)
Although the description and study of dialects used to be a central issue in traditional linguistics from the last quarter of the 19th century onwards, the protection and promotion of minority and regional languages only became a topic for linguistic research and language policy almost one hundred years later. With the rise of sociolinguistics in the sixties and seventies of the twentieth century and the growing interest in the language use of different social classes, linguists, educators and politicians became interested in non-standard languages. At the political level this led to several international reports, declarations, manifestos and charters, the most important being the Charter of Regional and Minority Languages accepted by the Council of Europe in 1992. In this article the implementation of the Charter in a few European Countries, such as France, Poland, Belgium and the Netherlands, is discussed. From this survey it becomes clear how political and legal factors prevail over linguistic arguments when it comes to the recognition of regional and minority languages. Not only the French unwillingness to recognize other languages in its territory other than standard French, but also the case of the Limburger language in Belgium and the Netherlands and that of Yiddish in the Netherlands and Sweden support this claim.